53 AMBULATORY BLOOD PRESSURE MONITOR IS SUPERIOR TO THE OFFICE BLOOD PRESSURE IN PREDICTING THE EARLY VASCULAR PATHOLOGY IN NON-HYPERTENSIVE YOUNG PROFESSIONALS. (10th December 2015) - Zhang, R.; Butterbaugh, G.; Aguilar, E.; Liao, J.; Rose, M.; Roques, B.; Thomson, J.; Donelon, S.; Reisin, E.
Abstract : Introduction: Office blood pressure (BP) has been the standard method for diagnosing and managing hypertension. However, studies found that 24-hr ambulatory BP monitor may be better than the office BP in predicting cardiovascular (CV) morbidity and mortality. The common carotid artery intima-media thickness (IMT) is a reliable and valid marker of CV disease process. We compare the association between IMT and the office and ambulatory systolic BP measures. Methods: As a part of our ongoing prospective study of job stress on CV diseases, a group of 88 non-hypertensive (BP < 140/90 mm Hg), clinically healthy young professionals (average 33 yo) were analyzed. A 24-hr ambulatory BP monitor (Spacelabs 90217-1A) was used to average the 24-hr systolic BP (24-SBP), which was further divided into systolic BP while working (work-SBP), awake but not working (leisure-SBP), and asleep (sleep-SBP). Office systolic BP (office-SBP) was calculated from three separate readings with standard method. Common carotid artery IMT was measured by ultrasonography (HP Sono 5500) and analyzed with IôDP software. Results: Using multivariable linear regression, we found work-SBP, sleep-SBP and 24-SBP to be significantly positively associated with increasing IMT. Neither leisure-SBP nor office-SBP was significantly associated with IMT. After adjusting for traditional contributing factors including age, gender, ethnicity, work shift, smoking history, waist circumference, fasting glucose, HDL, LDL, and CRP, work-SBP, sleep-SBP and 24-SBP remained significantly positively associated with IMT. Summary: Our results suggest that the average systolic BP from either 24-hr, limited working hours or asleep ambulatory monitor is more strongly associated with the early vascular changes than office BP or leisure-time BP. Therefore, ambulatory BP may be a better predictor of CV disease than office BP in the non-hypertensive healthy young professionals.